KAJIAN EKSPERIMENTAL PENGARUH VARIASI TEKANAN ELECTRIC FUEL PUMP TERHADAP DAYA, TORSI MESIN, EMISI GAS BUANG DAN KONSUMSI BAHAN BAKAR SEPEDA MOTOR INJEKSI - Ari Aryadi (Magister Teknik Mesin Universitas Pancasila, 2020)
This study aims to examine the effect of variations in the pressure of the electric fuel pump on the injection motor unit on the most effective power, exhaust emissions and fuel consumption efficiency, by adding a potentiometer to the electric fuel pump so that pressure variations can be changed from the standard value. This research was conducted by experimental testing, using the pressure independent variable of the electric fuel pump and the dependent variables were the vehicle performance, engine power, engine torque and exhaust emissions. The sample test equipment uses Sportdevice Dyno and Emission Tester. The pressure variations of the electric fuel pump tested are 270 kpa, 294 kpa, 350 kpa, 380 kpa at engine speed of 6000 rpm, 7000 rpm, 8000 rpm, 9000 rpm. The fuel used is Pertamax with RON 92. The results show that the highest power of 6.1 Horsepower (HP) at 6400 rpm to 6700 is obtained at a pressure of 294. The highest torque is 6.84 (Nm) at 6300 Rp. The lowest fuel consumption value is at 294 kPa 32.1 km / liter. . For CO testing, the lowest CO level was obtained at 0.68% at a pressure of 350 kPa. From the analysis of the average test data it can be concluded that four variations in pressure were carried out, the optimal results for power, engine torque and fuel consumption of injection motorbikes at pressures of 294 kPa and 350 kPa.